Scenario of Import And Export Of Bamboo Products in India - Upadhyay, V.K.; Nandanwar, Anand; Kushwaha, Pradeep; Murthy, Narsimha; Ranjan, Manish; Singh, M.P. (Indian Forester, 2023)
This study aims to examine the import and export of products made of bamboo other than incense sticks (Agarbatti). The evaluation is based on data on India’s import and export of bamboo-based products from 2015 to 2020. According to the findings of the study, India exported small bamboo sticks (88.68 per cent) and imported bamboo raw materials (76.4%). China and Vietnam exported the most bamboo products to India and United States, Germany, United Kingdom and Netherlands were India’s primary buyers. During the five years time frame, Incense sticks (Agarbatti) area covered 60% of Import and 69% of Commodity from India out of all bamboo items. Small bamboo sticks were the most widely exported item, while bamboo raw materials were the most widely imported product. China and Vietnam were major suppliers during this time, and the United States, Germany, the United Kingdom, and the Netherlands were major buyers.